Improving aerobic capacity through active videogames: A randomized controlled trial - Jorge Luiz de Brito-Gomes; Raphael José Perrier-Melo; Erik Anders Wikstrom; Manoel da Cunha Costa (Universidade Estadual Paulista (UNESP), 2015)
AbstractThe rate of peak workload improvement between different types of Active Video Games (AVG) in young sedentary adults was investigated. Aerobic capacity improvement after a 6-week intervention between AVG types was also compared. Twenty participants, after baseline assessments, were randomized into one of three parallel groups: structured AVG (n= 6), unstructured AVG (n= 7) and a control group (n= 7). Participants played their respective AVG 3 times a week for 6-weeks (30 minutes-session). The control group maintained normal activities. Both structured and unstructured AVG improved peak workload after four weeks but only the structured group maintained this improvement through week five and six. Aerobic capacity improved in the unstructured (Pre: 36.0 ± 5.2ml.kg.min-¹,Post: 39.7 ± 4.9ml.kg.min-¹, p = .038) and structured AVG (Pre: 39.0 ± 5.9ml.kg.min-¹,Post: 47.8 ± 4.3ml.kg.min-¹, p = .006) groups. Structured AVG provide greater health benefits to aerobic capacity and peak workload in young sedentary but otherwise healthy males relative to unstructured AVG.